Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Chapter 3 - 3.2 - Polynomial Functions of Higher Degree - 3.2 Exercises - Page 261: 59



Work Step by Step

$f(x)=a[x-(1+\sqrt 2)][x-(1-\sqrt 2)]=a[(x-1)-\sqrt 2][(x-1)+\sqrt 2]=a[(x-1)^2-(\sqrt 2)^2]=a(x^2-2x+1-2)=a(x^2-2x-1)$ $a$ can be any value. If $a=1$: $f(x)=x^2-2x+1-2=x^2-2x-1$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.